IMPLEMENTASI GELAR KARYA DAN POJOK BACA BERBASIS KEARIFAN LOKAL DALAM MENINGKATKAN LITERASI BUDAYA DI SDN 02 KADEMANGAN - Yulia Eka Yanti; Tety Nur Cholifah; Hendra Rustantono; Vika Cahya Intani; Niken Annur Habibah; Reka Revianti; Nur Aida Salsabila; Ridha Nazillatul Laili; Vivin Nur Kholifah; Hamidi Rasyid (FIP UNIRA MALANG, 2026)
At SDN 02 Kademangan, teaching and learning activities still introduce very little Lolak culture and traditions to students. Learning at school focuses more on academic aspects and does not provide sufficient space for the introduction and understanding of local cultural values. This activity not only aims to introduce and preserve local culture, but also to improve students' overall literacy skills. Apart from that, this program is also expected to encourage active participation by the community and parents in cultural education, as well as forming students' characters who love and appreciate their culture more. Implementation methods include planning and preparation, organizing and decorating the event, evaluating the work, closing and documenting. With this activity, students' reading interest in local culture-based material has increased. In addition to increasing cultural literacy, students' general literacy skills, such as reading, writing and speaking, also experience development. In the reading corner, students read folk tales and other materials, which not only enriches their knowledge but also improves their reading ability.